Une modélisation d’un zoom au moyen de microscopes virtuels - Antibi, André; Bair, Jacques; Henry, Valérie (Teaching Mathematics and Computer Science, 2004)
In this paper, we explain how a computer works when "zooms" are made around a point on a planar curve. This modelisation leads to an easy and algorithmic method to find the (vertical or not vertical) tangents for the studied curve.